Relative energy deficiency in sport (RED-S) in adolescents - A practical review - Gould, R. J.; Ridout, A. J.; Newton, J. L. (International Journal of Sports Medicine, 2023)
There are many immediate and longer-term physical, psychological and metabolic benefits of being active during adolescence. These benefits exist when exercise and physical activity are undertaken in a state of energy balance. When exercise occurs in an environment of low energy availability, this is currently termed relative energy deficiency in sport and there are potential significant negative effects on mental well-being, bone, endocrine and metabolic health. Therefore, relative energy deficiency in sport may present to many different specialists or allied health professionals depending upon the symptoms or reasons for seeking help, which include injury, such as bone stress or soft tissue problems, irregular or absent menstruation, stress, anxiety or low mood, or sporting underperformance as examples. The promotion of physical activity in adolescence is a critical part of public health strategy. In parallel with this positive public health message, there needs to be an increase in the awareness of, and education about, relative energy deficiency in sport for those working with and looking after adolescents.This review provides an up to date, practical evidenced based guide on the recognition, investigation and management of relative energy deficiency in sport in the adolescent, both male and female.